1991
DOI: 10.1007/bf00014776
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of very strong soils by seedling roots of different plant species

Abstract: The abilities of seedling roots of twenty-two plant species to penetrate a strong growth medium were compared under controlled conditions. Seedlings were grown for 10 days in compression chambers filled with siliceous sandy soil at 0.2kgkg -I water content and mean penetrometer resistance of 4.2MPa. Root elongation and thickening were measured after growth. The results show that soil strength reduced the elongation of roots of all plant species by over 90% and caused the diameters of the roots to increase comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
156
0
24

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(189 citation statements)
references
References 23 publications
9
156
0
24
Order By: Relevance
“…Uma evidência da influência da estrutura do solo na definição das condições físicas para o desenvolvimento radicular é que um solo deve apresentar acima de 10% de porosidade de aeração para oferecer condições favoráveis ao bom desenvolvimento radicular das plantas (Hanks & Thorp, 1956;Eavis, 1972) e, para alguns autores (Ehlers et al, 1983;Bengough & Mullins, 1990;Materechera et al, 1991), as culturas podem apresentar crescimento radicular em diferentes valores de resistência crítica. Boone et al (1987) demonstraram que, em solo compactado com alta resistência ou reduzida difusão de oxigênio, a restrição ao crescimento das plantas dependeu da distribuição pluviométrica, ou seja, das condições de umidade do solo.…”
Section: Resultsunclassified
“…Uma evidência da influência da estrutura do solo na definição das condições físicas para o desenvolvimento radicular é que um solo deve apresentar acima de 10% de porosidade de aeração para oferecer condições favoráveis ao bom desenvolvimento radicular das plantas (Hanks & Thorp, 1956;Eavis, 1972) e, para alguns autores (Ehlers et al, 1983;Bengough & Mullins, 1990;Materechera et al, 1991), as culturas podem apresentar crescimento radicular em diferentes valores de resistência crítica. Boone et al (1987) demonstraram que, em solo compactado com alta resistência ou reduzida difusão de oxigênio, a restrição ao crescimento das plantas dependeu da distribuição pluviométrica, ou seja, das condições de umidade do solo.…”
Section: Resultsunclassified
“…Responses such as a considerable increase in root diameter (e.g. Materechera et al, 1991) and closer lateral spacing (e.g. Goss & Russell, 1980), may well represent an extreme reaction to stress possibly only triggered when some critical threshold set of conditions has been exceeded.…”
Section: Lateral Diameter and Growth Ratementioning
confidence: 99%
“…The response of roots to mechanical impedance differs between species, varieties within a species, and stages of development. However, there are few direct comparisons of the sensitivity of roots to changes in soil physical conditions (Powell, 1989;Materechera, Dexter & Alston, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Place (2006) found 55% of Palmer amaranth (Amarnanthus palmeri) roots penetrated into loamy sand subsoil at 1.9 g/cm 3 . These species likely optimize three common plant responses to root impedance: 1) a decrease in turgor pressure in the region of elongation slowing the extension of the root cap (Atwell 1990), 2) an increase in radial turgor pressure immediately behind the root tip increasing root diameter (Materechera et al 1991, Clark et al 2003, and 3) lateral root proliferation (Gregory 2006). Among hormones, auxin and gibberellins have been shown to directly increase root growth (Gregory 2006), and ethylene has been suggested as playing a key role in mediating an increase in root diameter and a decrease in elongation rate (Clark et al 2003), while brassinolides have been shown to inhibit root growth (Chaiwanon and Wang 2015).…”
Section: Bulk Density and Texture Effects On Root Growthmentioning
confidence: 99%
“…It is likely the moderate bulk density and amount of clay within the subsoil was low enough to allow for healthy root growth (Bowen 1981) This likely provided greater structural integrity and resistance against soil compaction (Ghestem 2011). Ethylene, and the resulting radial turgor pressure immediately behind the root tips, likely increased RD (Materechera et al 1991, Clark et al 2003.…”
Section: Mechanism For Root-enhanced Infiltrationmentioning
confidence: 99%